1933
DOI: 10.1002/bjs.1800208005
|View full text |Cite
|
Sign up to set email alerts
|

Accidental ligation of the hepatic artery. Report of one case, with a review of the cases in the literature

Abstract: ACCIDENTAL ligation of the hcpatic artery is fortunately rare. Twenty-seven cases have been reported in the literature up to datc. The rarity of the lesion and the complete investigation carried out prompts the presentation of this report. CASE REPORT.W. W., male, age 49, was admitted to Dr. R. R . Graham's service of the Toronto General Hospital on Kov. 5 , 1930, with a right inguinal hernia, haemorrhoids, and a slight prolapse of the rectum. During the course of routine history and physical examination, a py… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0
3

Year Published

1952
1952
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(16 citation statements)
references
References 6 publications
0
13
0
3
Order By: Relevance
“…If, however, under certain conditions the oxygen requirements of the liver rise, or the oxygen saturation of the portal venous blood falls owing to an increased mesenteric oxygen consumption [e.g., during absorption (27) It is not possible from the present study to evaluate the late sequelae of ligation of the hepatic artery in man. The great individual variation in hepatic arterial blood flow found in our patients may, however, explain why the artery in some cases may be ligated without noticeable influence on the liver (34), while in other cases it is fatal (8). In the present short-term experiments the clamping of the hepatic artery in all cases seemed to be harmless.…”
Section: Methodsmentioning
confidence: 49%
See 1 more Smart Citation
“…If, however, under certain conditions the oxygen requirements of the liver rise, or the oxygen saturation of the portal venous blood falls owing to an increased mesenteric oxygen consumption [e.g., during absorption (27) It is not possible from the present study to evaluate the late sequelae of ligation of the hepatic artery in man. The great individual variation in hepatic arterial blood flow found in our patients may, however, explain why the artery in some cases may be ligated without noticeable influence on the liver (34), while in other cases it is fatal (8). In the present short-term experiments the clamping of the hepatic artery in all cases seemed to be harmless.…”
Section: Methodsmentioning
confidence: 49%
“…Great differences have been found from one species to another (6,7), and our knowledge of the significance of the arterial blood supply to the human liver is limited mainly to observations of the late effect of occlusion of the hepatic artery (8) or of the portal vein (9,10). As these events are followed by compensatory changes in the hepatic circulation (11,12), no definite conclusions regarding the physiological role of the hepatic artery can be made on this basis.…”
mentioning
confidence: 99%
“…Bei der Ausschaltung der arteriellen Blutzufuhr steigt die hepatische Extraktion des Sauerstoffes aus dem Pfortaderblut und h~lt somit die metabolischen Anforderungen der Leber aufrecht, wobei die Durchflul3rate und der Sauerstoffpartialdruck der Pfortader nicht wesentlich ver/indert werden [1,23]. B. Operationsschock, Hypoxie, Septik~mie, Gallengangsocclusionen u. a. ist die alleinige Sauerstoffversorgung durch die Pfortader nicht ausreichend [9]. B. Operationsschock, Hypoxie, Septik~mie, Gallengangsocclusionen u. a. ist die alleinige Sauerstoffversorgung durch die Pfortader nicht ausreichend [9].…”
Section: Diskussionunclassified
“…traumatische Durchtrennungen der Leberarterie mit teils fatalen, teils komplikationslosen Verlauf beobachten [8,9]. traumatische Durchtrennungen der Leberarterie mit teils fatalen, teils komplikationslosen Verlauf beobachten [8,9].…”
unclassified
“…Two cases of hepatic aneurysm were recorded by Grant, Fitts, and Ravdin (1950) with ligation of the hepatic artery but both were fatal. Graham and Cannell (1933) reported a case of accidental ligation of the hepatic artery and reviewed the literature of 27 such cases. They concluded that hepatic artery ligation, although potentially serious, was not necessarily fatal.…”
mentioning
confidence: 99%